Terapi Tadabbur Al-Qur'an untuk Mengurangi Kecemasan Menghadapi Persalinan Pertama - Dini A.P. Prapto; Fuad Nashori; Rumiani Rumiani (Universitas Islam Indonesia, 2015)
During pregnancy, women experience significant changes in physiological and psychological functions. The research data shows that the process of pregnancy becomes a source of anxiety. This study aimed to examine the effect of Al-Qur'an Tadabbur therapy to reduce anxiety on the first delivery. Subjects are two groups of pregnant women. Measuring instruments used in this study is the Maternal Anxiety Scale were given before and after treatment and during follow-up. The first group received Al-Qur'an Tadabbur therapy, while the second group was the control group (waiting list). The difference (gain score) of pre-test, post-test and follow-up were compared by using Mann-Whitney analysis to determine whether there are significant differences in anxiety gain score. The result is the group who followed the Al-Qur'an Tadabbur therapy has lower anxiety score, p = 0.032 (p<0.05) compared with the control group. This study shows that Al Quran Tadabbur therapy can be used as one of the way to reduce anxiety before delivery. Key Words : Anxiety, Al-Qur'an Tadabbur Therapy, Pregnancy